Supplementary material from "Upper beak depression instead of elevation dominates cranial kinesis in woodpeckers" - Lyons, Sebastián (2023)
The value of birds’ ability to move the upper beak relative to the braincase has been shown in vital tasks like feeding and singing. In woodpeckers, such cranial kinesis has been thought to hinder pecking as delivering forceful blows calls for a head functioning as a rigid unit. Here, we tested whether cranial kinesis is constrained in woodpeckers by comparing upper beak rotation during their daily activities such as food handling, calling and gaping with those from closely related species that also have a largely insectivorous diet but do not peck at wood. Both woodpeckers and non-woodpecker insectivores displayed upper beak rotations of up to 8 degrees. However, the direction of upper beak rotation differed significantly between the two groups, with woodpeckers displaying primarily depressions and non-woodpeckers displaying elevations. The divergent upper beak rotation of woodpeckers may be caused either by anatomical modifications to the craniofacial hinge that reduce elevation, by the caudal orientation of the mandible depressor muscle forcing beak depressions, or by both. Our results suggest that pecking does not result in plain rigidification at the upper beak's basis of woodpeckers, but it nevertheless significantly influences the way cranial kinesis is manifested.